Firehose of Falsehood Propaganda Model in the 2019 Indonesian Presidential Election - Aminulloh, Akhirul; Artaria, Myrtati Dyah; Surya, Yuyun Wahyu Izzati; Qorib, Fathul; Hakim, Lukman (MediaTor (Jurnal Komunikasi), 2022)
The general election is a democratic means to gain power constitutionally. Several groups, however, use all the possible means to achieve that power. Firehose of falsehood is an example of political propaganda models that use every means to influence public opinion. This model of political propaganda finds its momentum through propaganda on social media. The purpose of this research is to understand the model of the firehose of falsehood on social media in the 2019 Indonesian presidential election. This research method uses a discourse analysis approach to identify the phenomena and events regarding the use of political propaganda on social media. Meanwhile, data collection is carried out through Twitter social media documentation. The results of this analysis indicated that the Firehose of Falsehood propaganda model was used as a political propaganda in the 2019 Indonesian presidential election. Social media, especially Twitter, became a means of propaganda to influence public opinion. The message delivery models were carried out through several methods. First, they were disseminated massively through various channels; second, they were carried out continuously and repeatedly; third, they were not following objective facts; and fourth, the media were lack of consistency.